Pengaruh Motivasi Kerja Dan Pendidikan Pelatihan Terhadap Kinerja Pegawai: Studi pada Puskesmas Mangunjaya Kabupaten Pangandaran - Iwan Hermawan; Irma Bastaman; Ferey Herman (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Employee performance at the Mangunjaya Health Center, Pangandaran Regency is quite good with an achievement of 75.82%. And based on the results of observations at the Mangunjaya Health Center, Pangandaran Regency, it was found that employee performance was not optimal, there were delays in completing work and the work results achieved were not in accordance with the standards that had been set. Then the performance of this employee is also influenced by motivation that is not optimal due to the lack of dedication and loyalty of employees even though they have received a decent salary and the level of promotion for employees who have not been optimal. Employee performance is also influenced by education and training that is not optimal, this is because the abilities and skills possessed by employees do not match the work position given and employees have not fully mastered the work produced. This study aims to study, find out, and analyze (1) The effect of work motivation on employee performance at the Mangunjaya Health Center, Pangandaran Regency. (2) The effect of education and training on employee performance at the Mangunjaya Health Center, Pangandaran Regency. (3) The effect of work motivation and education and training on employee performance at the Mangunjaya Health Center, Pangandaran Regency. This type of research is an explanatory survey, while the technical data analysis is validity test, reliability test, descriptive statistics, Inductive Statistical Analysis (Inferential) with Multiple Regression. The results of the study inform that (1) Motivation has a positive and significant effect on employee performance at the Mangunjaya Health Center, Pangandaran Regency. This means that if motivation is increased, then employee performance at the Mangunjaya Health Center, Pangandaran Regency will also increase. (2) Training education has a positive and significant effect on employee performance at the Mangunjaya Health Center, Pangandaran Regency. This means that if training education is increased, then employee performance at the Mangunjaya Health Center, Pangandaran Regency will also increase. (3) Motivation and training education have a positive and significant effect on employee performance at the Mangunjaya Health Center, Pangandaran Regency. This means that if motivation and training education are increased, then employee performance at the Mangunjaya Health Center, Pangandaran Regency will also increase.